The Integration of Eco-Sufism in Islamic Education at the Elementary Level - Achmad Junaidi; Khairil Anwar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: This study explores the integration of eco-Sufism into Islamic education at the elementary level as a strategic response to contemporary environmental crises and moral decline. Eco-Sufism, which blends spiritual values rooted in Sufism with ecological consciousness, offers a holistic framework to enhance Islamic education by fostering character development and environmental responsibility. This research aims to analyze how Sufi values—categorized into ethical, practical, and philosophical dimensions can be effectively incorporated into elementary-level Islamic education to shape students who are spiritually grounded and ecologically aware. This study employs a descriptive qualitative approach using thematic analysis, supported by library research. Literature on Islamic education, eco-Sufism, and relevant Qur'anic concepts such as ulul albab was reviewed and interpreted to develop an integrative educational model. The results indicate that Sufi-based education significantly contributes to students' moral and spiritual growth while promoting sustainable environmental behavior. Values such as zuhud (asceticism), tawakkul (trust in God), and muhasabah (self-reflection) are shown to enhance students' ecological sensitivity and encourage practices aligned with environmental stewardship. Furthermore, eco-pesantren practices, curriculum reforms, and Sufi-inspired pedagogical approaches support a paradigm shift toward integrative, value-based education. However, the study also identifies limitations in previous research, particularly the lack of empirical frameworks to assess the practical implementation of eco-Sufism in schools. This study proposes a contextually relevant model that combines Islamic identity reinforcement with environmental education, aiming to produce an intellectually capable, spiritually mature, and ecologically responsible generation.